2018
DOI: 10.3390/nu10121892
|View full text |Cite
|
Sign up to set email alerts
|

Health Effects of Resveratrol: Results from Human Intervention Trials

Abstract: The effect of resveratrol (RV) intake has been reviewed in several studies performed in humans with different health status. The purpose of this review is to summarize the results of clinical trials of the last decade, in which RV was determined in biological samples such as human plasma, urine, and feces. The topics covered include RV bioavailability, pharmacokinetics, effects on cardiovascular diseases, cognitive diseases, cancer, type 2 diabetes (T2D), oxidative stress, and inflammation states. The overview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
162
1
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(168 citation statements)
references
References 66 publications
1
162
1
4
Order By: Relevance
“…RE intake has pleiotropic effects in humans [181]. Although it is generally well tolerated, some adverse effects including nephrotoxicity and gastrointestinal problems were reported in human subjects [182,183].…”
Section: Human Trials With Resveratrolmentioning
confidence: 99%
“…RE intake has pleiotropic effects in humans [181]. Although it is generally well tolerated, some adverse effects including nephrotoxicity and gastrointestinal problems were reported in human subjects [182,183].…”
Section: Human Trials With Resveratrolmentioning
confidence: 99%
“…The contrasting results suggest that in order to obtain beneficial effects, the dose and the way of administration have to be carefully analyzed. It was suggested that a moderate (>450 mg) continuous intake is better than a single, higher dose administration [145].…”
Section: Stilbenesmentioning
confidence: 99%
“…Although RES can prevent oxidative stress and inflammation, there is a disagreement regarding its beneficial effects on cardiovascular markers and endothelial dysfunction and in type 2 diabetes patients. The contrasting effects of RES reported in different studies could be explained in terms of different factors, including doses, administration medium and form, age, gender, health status of the intestinal microbiota and its pharmacokinetics [38]. The pharmacokinetic properties of RES are less acceptable and limit its success.…”
Section: Introductionmentioning
confidence: 99%